PENERAPAN ANALISIS KONTEN KUALITATIF PADA STUDI REVISIT INTENTION WISATAWAN MUSLIM KE LOMBOK DALAM KONTEKS PARIWISATA HALAL - Dhanny Safitri; Akhmad Saufi; Dwi Putra Buana Sakti (Master of Management, Mataram University, 2022)
Content analysis is one of the data analysis methods in qualitative research which can be applied in various fields of study. This method is known for its advantages and flexibility in analyzing various text data. By using content analysis, especially the inductive approach, this article tries to explain how to conduct and apply a qualitative content analysis to research issues that is still fragmented, such as investigating the factors of Muslim tourists' revisit intention to Lombok in the context of halal tourism. The main stages described in this paper are: open coding, recontextualization, and categorization and compilation. In addition, this article also explained how to present and interpret the data that has been analyzed. It is hoped that the explanation of this article can help other researchers who want to use inductive qualitative content analysis in the field of management and/or tourism studies, or other studies where the topics researched are still limited or fragmented. Keywords: qualitative content analysis, analysis method, revisit intention, halal tourism